From phenotypes to endotypes to asthma treatment - Agache, Ioana O (Current opinion in allergy and clinical immunology, 2013)
The current guidelines for asthma diagnosis and management do not recognize that different phenotypes of asthma exist, with significant variations in the manifestation of airway inflammation, symptoms, severity, and response to treatment. This article will critically review new approaches to classify asthma together with the emerging endotype-driven therapeutic strategies. Several new approaches for classifying asthma are available, from precision and deep phenotyping to identification of novel causal pathways and translation of biomarkers into pathway-specific diagnostic tests. New phenotypes, such as epigenetic phenotypes, asthmatic granulomatosis, or neurophenotypes are described. Large clinical trials testing the endotype-driven approach are increasingly successful, but the dissociated effect and the drug efficacy at the target site remain unsolved issues. Profiling the Th2 low and the resident cell compartment of asthma are major unmet needs in asthma endotyping. Each of the hallmark characteristics of asthma (inflammation, remodeling, airway hyperreactivity) is the expression of a complex network of molecules, very diverse both within any given patient in time and between any two patients. Some of these networks are repetitive across individuals with asthma and specific for clinical expression, gene-environment interaction and inflammatory cell profiles represent novel endotype-specific diagnostic and therapeutic strategies.